Moderate Factor XII Deficiency - Bok, J; Veltkamp, J. J; Loeliger, E. A (Thrombosis and Haemostasis, 1965)
A case of “moderate” factor XII deficiency, with 3.6% factor XII activity, is reported. Because the activity of factor XII found in the parents of the patient is consistent with heterozygousity, the defect may be considered hereditary.